Disruption of Saturn's quasi-periodic equatorial oscillation by the great northern storm. (November 2017) - Fletcher, Leigh; Guerlet, Sandrine; Orton, Glenn; Cosentino, Richard; Fouchet, Thierry; Irwin, Patrick; Li, Liming; Flasar, F.; Gorius, Nicolas; Morales-Juberías, Raúl
Abstract The equatorial middle atmospheres of the Earth1, Jupiter2 and Saturn3, 4 all exhibit a remarkably similar phenomenon—a vertical, cyclic pattern of alternating temperatures and zonal (east–west) wind regimes that propagate slowly downwards with a well-defined multi-year period. Earth's quasi-biennial oscillation (QBO) (observed in the lower stratospheric winds with an average period of 28 months) is one of the most regular, repeatable cycles exhibited by our climate system1, 5, 6, and yet recent work has shown that this regularity can be disrupted by events occurring far away from the equatorial region, an example of a phenomenon known as atmospheric teleconnection7, 8 . Here, we reveal that Saturn's equatorial quasi-periodic oscillation (QPO) (with an 15-year period3, 9 ) can also be dramatically perturbed. An intense springtime storm erupted at Saturn's northern mid-latitudes in December 201010–12, spawning a gigantic hot vortex in the stratosphere at 40° N that persisted for three years13 . Far from the storm, the Cassini temperature measurements showed a dramatic 10 K cooling in the 0.5–5 mbar range across the entire equatorial region, disrupting the regular QPO pattern and significantly altering the middle-atmospheric wind structure, suggesting an injection of westward momentum into the equatorial wind system from waves generated by the northern storm. Hence, as on Earth, meteorological activity at mid-latitudes can have a profound effect on the regular atmospheric cycles in Saturn's tropics, demonstrating that waves can provide horizontal teleconnections between the phenomena shaping the middle atmospheres of giant planets. The 2010–2011 storm that appeared at Saturn's northern mid-latitudes significantly altered the wind structure and atmospheric temperature even far away from the storm, by disrupting the quasi-periodic atmospheric oscillations at the equator for more than 3 years.